Fortuna, fatalismo, libertad: el giro maquiaveliano - Forte, Juan Manuel (ENDOXA, 2002)
The main concern of this article is the analysis of Machiavelli’s notion of fortune, intimately connected to his notion of virtue and his understanding of politics. The first objetive is to evalúate the essential distinction between fortune in universale and fortune "in particulare". I will claim that almost all scholars have confused this crucial Machiavellian distinction, and it is therefore a source of inaccuracies and misinterpretations. The second objective is to outline the theoretical limitations of some naturalistic and astrological interpretations of Machiavelli’s concept of fortune. The third objective to will be to argüe that it is impossible to decide whether Machiavelli is compromised with a conception of fortune as simply tyche (in the sense of subjective ignorance of the causes implied in an effect), or rather as automáton (in the Aristotelian meaning of objetive indeterminacy and accidental causes). Lastly, I will try to evaluate the importace of the relevance - argued by some scholars — of certain correspondences between the Florentine’s naturalism and the «modemity» of his political thought.